Cystic Teratoma of Face and Scalp - Management of Difficult Pediatric Airway by Modification of Conventional Technique - Mona Arya; J S Dali; Farah Hussain; Yogesh Kumar Sarin (EL-Med-Pub, 2017)
Management of pediatric difficult airway has always been a challenge to the anesthesiologist. Effective airway management includes proper assessment of the airway, anticipation of difficulties, good preparation & team work. We present a unique case of 6-week-old infant posted for excision of a large cystic teratoma of face and scalp where the airway was secured effectively by using the retro-molar intubation and modification of conventional technique of ventilation and laryngoscopy.